EFFECT OF SUPPLEMENTARY FEEDING OF CREEP FEED IN PATTANAMADU SHEEP LAMBS UNDER FIELD CONDITIONS IN THE BREEDING TRACT OF TAMIL NADU - M. Sundaramoorthy; N. Kumaravelu; Thanga Thamil Vanan; A. Serma Saravana Pandian (Indian Journal of Veterinary and Animal Sciences Research, 2025)
A study on effect of supplementary feeding of creep feed in Pattanam sheep lambs was conducted in its breeding tract of Tamil Nadu, India. Total number of 90 Pattanam sheep lambs at the age of one month were selected in the farmers flock and divided into three groups each comprising of 30 lambs, assigned to the following treatments and reared upto three months. In T-1 (control) 30 lambs were maintained by routine feeding management by farmers, in T-2 30 lambs were fed with concentrate supplementation at the rate of 50 gms per lamb per day along with routine feeding management by farmers and in T-3 30 lambs were reared by concentrate feeding at the rate of 50 gms per lamb per day with mineral supplementation through salt lick block along with routine feeding management by farmers. Fortnightly body weight (kg) and average daily gain (gms) was recorded to assess the influence of supplementation on growth rate of lambs in farmers flock. At start of the trial the overall body weight of lambs was 8.45 ± 0.91 which was non-significant. Fortnightly body weight was 9.78 ± 2.21, 10.98 ± 1.54, 11.77± 1.73 and 12.09 ± 1.73 in first, second, third and fourth fortnights respectively. Between groups significant difference (P< 0.05) in body weight gain was observed in first fortnight and highly significant difference (P< 0.01) was observed during subsequent fortnight. Average daily gain (g) was recorded as 88.67, 80.00, 52.67 and 26.00 during first, second, third and fourth fortnight, respectively. It can be observed that the lambs under T3 had superior ADG followed by the lambs under T2 and T1.